Kelayakan Fisik Sediaan Toner dari Ekstrak Daun Sirih Cina (Peperomia pellucida) dengan Variasi Surfaktan - Pratiwi, Ulfa Mawaddah; Achmadi, Taofan Ali; Setyowati, Erna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the physical feasibility of toner preparations from Chinese betel leaf extract (Peperomia pellucida) with variations of polysorbate 20 surfactants through organoleptic tests. Toner is a form of liquid cosmetic preparation used to cleanse, refresh, and balance the pH of the skin. Chinese betel leaf extract contains active compounds such as flavonoids, tannins, and saponins that function as antibacterials and anti-inflammatory agents. Polysorbate 20 is used as a nonionic surfactant that plays a role in maintaining the clarity and stability of the solution. This study used an experimental method with a quantitative approach. Three toner formulations were prepared, namely F1 (without extract and containing 5 mL of polysorbate 20), F2 (5 grams of extract and 5.5 mL of polysorbate 20), and F3 (7.5 grams of extract and 6 mL of polysorbate 20). Organoleptic tests were carried out by expert panelists (two beauty lecturers and one doctor) based on color, aroma, and texture parameters. The test results showed that F1 had a clear color and was odorless, while F2 and F3 had a brownish green color and a distinctive aroma of Chinese betel leaves. All three formulations had a liquid texture. The highest organoleptic test score was obtained by F3 (83.33) which indicated that the formulation with the highest concentration of extract and surfactant provided the best visual and sensory impression. The conclusion of this study indicated that F3 was the most physically feasible formulation based on organoleptic evaluation. This study contributes to the development of local herbal cosmetics that are stable and sensorially preferred.